2018
DOI: 10.4103/jrms.jrms_879_17
|View full text |Cite
|
Sign up to set email alerts
|

Serum-based microRNA biomarkers for major depression: MiR-16, miR-135a, and miR-1202

Abstract: Background:Depression is a common medical condition with a high prevalence leading to emotional abnormality. Despite some drawbacks, depression currently diagnosed using a combination of patient interviews and self-report questionnaires. Recently, there is emerging emphasis to establish biomarkers to diagnosis and clinical management of depression. This case–control study was designed to develop microRNA (miRNA)-based serum biomarker for depression.Materials and Methods:In this study, 39 patients with depressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
39
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 63 publications
(43 citation statements)
references
References 29 publications
3
39
1
Order By: Relevance
“…One study indicated that serum levels of miRNA-16 are increased in rats after CUMS [60]. In contrast, clinical reports revealed that serum levels of miRNA-16 are reduced in patients with depression [43]. In the present study, we found the disease model caused overall upregulated miRNA-16 levels in the hippocampus but did not significantly affect serum miRNA-16 levels.…”
contrasting
confidence: 67%
See 1 more Smart Citation
“…One study indicated that serum levels of miRNA-16 are increased in rats after CUMS [60]. In contrast, clinical reports revealed that serum levels of miRNA-16 are reduced in patients with depression [43]. In the present study, we found the disease model caused overall upregulated miRNA-16 levels in the hippocampus but did not significantly affect serum miRNA-16 levels.…”
contrasting
confidence: 67%
“…However, few studies have focused on serum levels of miRNA-16 in patients with depression. A recent study reported that the level of serum miRNA-16 was significantly decreased in patients with depression, which suggests that miRNA-16 has potential as a high-specificity and highsensitivity biomarker for depression [43]. e present study aimed to answer the following question: what is the relationship between miRNA-16 and 5-HT in the hippocampus and serum?…”
Section: Introductionmentioning
confidence: 91%
“…ID J:208678). Both the miRs are decreased in the blood of MDD patients [120], which corresponds to an increased level of GSK3β [39]. Moreover, miR16 regulates the expression of 5-HT transporter (SERT) [121], while miR135a is associated with the regulation of the expression of SERT and 5-HT 1A R [122].…”
Section: β-Catenin Destruction Complexmentioning
confidence: 99%
“…Much effort has been devoted to developing effective therapeutic agents. Recently, targeting microRNAs (miRNAs) with small molecules has become a novel therapy for human diseases (Gheysarzadeh et al, 2018). In other research, Meng et al, present a systematic computational approach to construct a bioactive Small molecule and miRNA association Network in AD (SmiRN-AD), which is based on the gene expression signatures of bioactive small molecule perturbation and AD-related miRNA regulation.…”
Section: Other Ad Treatment Productsmentioning
confidence: 99%